Investigation of in-situ ion release and surface film formation of hcp Mg-Li thin films - Hanke, Lisa; Kalchgruber, Lukas; Westernströer, Ulrike; Garbe-Schönberg, Dieter; Quandt, Eckhard; Valtiner, Markus (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
In this work, the dissolution process of magnetron sputtered Mg-Li thin films was investigated by in-situ flow cell/ICP-MS measurements and ex-situ ICP-MS measurements after longer immersion and additional XPS measurements. High Li concentrations are released due to a Li rich carbonate layer formed in air. The depletion of Li leads to preferred Mg release before preferred Li release occurs due to the higher activity of Li and incorporation of Mg in corrosion products. This data provides a baseline for developing release profiles for medical application, more generally, it unravels details of the corrosion mechanism of lightweight MgLi alloys.
Keywords: A Magnesium; A Sputtered films; B XPS; C Surface films; B ICP- MS